Information about the III All-Ukrainian symposium with international participation "Morphogenesis of organs and tissues under the influence of exogenous factors" - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2010)
October 7-9, the traditional symposium "Morphogenesis of organs and tissues by the influence of exogenous factors" took place in Alushta, on the basis of the "Golden Spit" boarding house.